Isolation, characterisation, and lipase production of a cold-adapted bacterial strain Pseudomonas sp. LSK25 isolated from Signy Island, Antarctica - Salwoom, Leelatulasi; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Mohd Shariff, Fairolniza; Convey, Peter; Pearce, David; Mohamad Ali, Mohd Shukuri (MDPI, 2019)
In recent years, studies on psychrophilic lipases have been an emerging area of research in the field of enzymology. This study focuses on bacterial strains isolated from anthropogenically-influenced soil samples collected around Signy Island Research Station (South Orkney Islands, maritime Antarctic). Limited information on lipase activities from bacteria isolated from Signy station is currently available. The presence of lipase genes was determined using real time quantification PCR (qPCR) in samples obtained from three different locations on Signy Island. Twenty strains from the location with highest lipase gene detection were screened for lipolytic activities at a temperature of 4 °C, and from this one strain was selected for further examination based on the highest enzymatic activities obtained. Analysis of 16S rRNA sequence data of this strain showed the highest level of sequence similarity (98%) to a Pseudomonas sp. strain also isolated from Antarctica. In order to increase lipase production of this psychrophilic strain, optimisation of different parameters of physical and nutritional factors were investigated. Optimal production was obtained at 10 °C and pH 7.0, at 150 rev/min shaking rate over 36 h incubation.